KEMANDIRIAN KOMUNIKASI WARGA DESA PANGGARANGAN DALAM LINGKUP KEBENCANAAN - Albertus Magnus Prestianta; Irwan Fakhruddin; Agus Kustiwa (Universitas Pelita Harapan, 2023)
As a country located in the Circum-Pacific Belt area, Indonesia is vulnerable to natural disasters such as earthquakes and tsunamis. A research mentioned that there would be a potential tsunami with a maximum height of 20 meters in the south of Java Island. Community preparedness in dealing with potential disasters is essential and has a high level of urgency. UMN partnered with the South Lebak Mitigation Group (GLMS) to organize disaster literacy strengthening activities to meet the Tsunami Ready indicators, primarily the preparedness component for disseminating information. This activity emphasizes disaster communication to increase public awareness and knowledge of the importance of disaster mitigation. The target participants and locus of activity are Panggarangan Village, Panggarangan District, and Lebak Regency, residents. Activities include research on citizen disaster literacy mapping, deployment of communication product, and citizen journalism training. The results of the mapping research show that information about disasters with local content is still limited in terms of quantity and quality. To that end, each communication product was made to fit the local context of the South Lebak community. Furthermore, media literacy and citizen journalism training was held so local communities could produce and fulfil their own information needs.abstract in bahasaIndonesia sebagai negara yang berada pada area Circum-Pasific Belt rentan mengalami bencana alam gempa bumi dan tsunami. CEST (Center for Earthquake Science and Technology) ITB menyebutkan akan adanya potensi tsunami dengan ketinggian maksimal 20 meter di selatan Pulau Jawa. Kesiapsiagaan masyarakat dalam menghadapi potensi bencana sangatlah diperlukan dan tinggi tingkat urgensinya. UMN bermitra dengan Gugus Mitigasi Lebak Selatan (GLMS) menyelenggarakan kegiatan penguatan literasi kebencanaan guna memenuhi indikator Tsunami Ready khususnya komponen kesiapsiagaan dalam hal penyebaran informasi. Kegiatan ini menaruh titik tekan pada komunikasi kebencanaan dengan tujuan meningkatkan kesadaran dan pengetahuan warga akan pentingnya mitigasi bencana, tanggap darurat dan pemulihan pasca terjadi bencana. Target peserta dan lokus kegiatan adalah warga Desa Panggarangan, Kecematan Panggarangan, Kabupaten Lebak. Kegiatan yang dilakukan meliputi riset pemetaan literasi kebencanaan warga, pembuatan konten komunikasi, dan pelatihan jurnalisme warga. Hasil riset pemetaan menunjukkan bahwa informasi seputar kebencanaan yang bermuatan lokal masih terbatas dalam hal jumlah dan kualitas. Untuk itu, konten komunikasi dibuat menyesuaikan dengan konteks lokal masyarakat Lebak Selatan. Selanjutnya, pelatihan literasi media dan jurnalisme warga digelar agar masyarakat lokal dapat memproduksi dan memenuhi kebutuhan informasinya sendiri.